2019
DOI: 10.1007/s11292-019-09379-w
|View full text |Cite
|
Sign up to set email alerts
|

Measurement bias in self-reports of offending: a systematic review of experiments

Abstract: Objectives Self-reported offending is one of the primary measurement methods in criminology. In this article, we aimed to systematically review the experimental evidence regarding measurement bias in self-reports of offending. Methods We carried out a systematic search for studies that (a) included a measure of offending, (b) compared self-reported data on offending between different methods, and (c) used an experimental design. Effect sizes were used to summarize the results. Results The 21 pooled experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
0
22
1
Order By: Relevance
“…More recently, Gomes et al . [8] focused more narrowly on reports on offending. Of the 10 studies comparing paper SAQs with CASI, five comparisons favored CASI; only one reached statistical significance at the α = 0.05 level.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Gomes et al . [8] focused more narrowly on reports on offending. Of the 10 studies comparing paper SAQs with CASI, five comparisons favored CASI; only one reached statistical significance at the α = 0.05 level.…”
Section: Introductionmentioning
confidence: 99%
“…Second, whilst we suggest that in the present case, direct questioning elicited the best results, we do not suggest that these are not also subject to self‐reporting biases. Gomes et al recently conducted a systematic review of measurement biases in self‐reports of offending behavior and demonstrated the range of potential biases that may occur under varying conditions. No design will be absent of these, however, some may be more suited to certain study designs than others, as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…One factor in explaining the degree of misreporting in direct questioning is the mode of survey delivery (see Ref. for a systematic review). Interviewer‐administered surveys, such as pencil‐and‐paper studies, or face‐to‐face interviews, can result in increased misreporting compared to self‐administered surveys.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we also noticed that behavioral outcomes were rare, mainly measured through self-report not objective data. While self-reported information on criminal activity is influenced by measurement bias, objective data are limited to official records, disregarding unreported criminal actions (Baier et al, 2016;Gomes et al, 2019). Coupled with the fact that only few people engage in violent extremism at all, assessing such behavior is a difficult task (Clubb & Tapely, 2018;Mastroe & Szmania, 2016).…”
Section: Discussionmentioning
confidence: 99%